Reflective pondering is associated with a global cognitive marker of Alzheimer's disease risk: Neuropsychiatry and behavioral neurology: The neuropsychiatry of subjective cognitive disorder and prodromal AD. (7th December 2020) - Demnitz‐King, Harriet; Whitfield, Tim; Schlosser, Marco; Barnhofer, Thorsten; Collette, Fabienne; Klimecki, Olga; Lutz, Antoine; Schild, Ann‐Katrin; Wirth, Miranka; Chetelat, Gael; Marchant, Natalie L; Group, Medit‐Ageing Research
Abstract: Background: Reflective pondering is an introspective mechanism conceptualised as actively seeking a solution to one's problems. Literature has consistently demonstrated positive associations between reflective pondering and improved mental health outcomes in clinical populations. Given that poor mental health (e.g. depression, anxiety) has been associated with increased dementia risk, and that reflective pondering improves mental health, we asked whether reflective pondering could also act as a protective factor against dementia, measured by cognitive function, in older adults. Method: Baseline data from 145 older adults with subjective cognitive decline (SCD; mean age = 72.2) from the SCD‐Well clinical trial and 135 healthy older adults (mean age = 70.5) from the Age‐Well clinical trial were included in this study. All participants completed the reflective pondering subscale of the Rumination Response Scale and a modified version of the Preclinical Alzheimer's Cognitive Composite (PACC; Donohue et al., 2014). Linear regressions were run to determine the association between reflective pondering and PACC scores in each cohort independently. Analyses controlled for available prognostic characteristics known to be associated with Alzheimer's disease (e.g. age, sex, education, depressive symptoms and APOE genotype). Result: In SCD‐Well reflective pondering was positively associated with PACC scores after controlling for age, sex, education and depressive symptoms ( β = 0.05, p <.01), with higher levels of reflective pondering associated with better cognition. Similarly, in Age‐Well reflective pondering was also positively associated with PACC scores ( β = 0.04, p = .03) aftercontrolling for age, sex, education, depressive symptoms and APOE genotype. Conclusion: In two independent cohorts that included healthy older adults and individuals with SCD, levels of reflective pondering were positively associated with a global cognitive marker of Alzheimer's risk. Our results introduce preliminary support for reflective pondering as a protective factor for cognitive function. Both SCD‐Well and Age‐Well are clinical trials, thus future work will evaluate the association between changes in reflective pondering due to intervention and cognitive function.